A Gas Sensor With Fe2O3 Nanospheres Based on Trimethylamine Detection for the Rapid Assessment of Spoilage Degree in Fish - Liu, Likun; Fu, Shuang; Lv, Xiao; Yue, Liling; Fan, Li; Yu, Haitao; Gao, Xiuli; Zhu, Wenbin; Zhang, Wei; Li, Xin; Zhu, Wenquan (Frontiers in Bioengineering and Biotechnology, 2020)
A spherical iron oxide precursor was prepared using a solvothermal method, and then treated thermally at 400 °C to obtain α-Fe2O3 nanoparticles. The structures and morphology of the as-obtained products were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The results showed that the diameter of the α-Fe2O3 nanoparticles was approximately 500 nm. In addition, we formed the α-Fe2O3 nanoparticles into a thick film as a gas sensor and performed a gas sensing test. When the working temperature was set at 250 °C, the α-Fe2O3 nanoparticle displayed very good selectivity and high sensitivity for trimethylamine (TMA). The minimum detection was as low as 1 ppm, and the response value for 100 ppm TMA gas was 27.8. Taken together, our findings illustrated that the α-Fe2O3 nanoparticles could be used as a gas-sensitive material to test the freshness of fish.